Nursing students’ lived experiences with using AIDET in patient communication: A qualitative study in the Philippines - Madayag, Rudena A.; Esteron, Jeffrey V.; Lozano, Dianne Anne A.; Bautista, Evangeline C.; Fernandez, Zenaida S.; Ramirez, Debbie Q. (Belitung Raya Publisher - Belitung Raya Foundation, 2024)
Background: Effective communication is vital in nursing, influencing patient safety, satisfaction, and care quality. The AIDET framework is a proven tool for reducing patient anxiety and enhancing their experience. However, perceptions and experiences of Filipino nursing students with AIDET remain unexplored. Objective: This study explored Filipino nursing students’ use of AIDET, focusing on benefits, challenges, and improvements. Methods: A qualitative, interpretive phenomenological approach informed by the philosophy of Martin Heidegger was employed. This 2023 study, conducted at a university in Angeles City, Philippines, explored Filipino nursing students’ experiences with the AIDET communication framework. Thirty participants were purposefully selected to participate in facilitated discussions following a semi-structured interview guide. Thematic content analysis of the transcribed audio recording identified recurring themes in their narratives, focusing on the meanings they ascribed to their experiences using AIDET. Results: Four themes emerged: (a) Streamlined nurse-patient interaction (organizes communication, rapport building, alleviate anxiety, acknowledgment, and empowerment as sub-themes), (b) Enhances patient-centered care (empathy and compassion, improved patient experience as sub-topics), (c) Challenges with specific patient populations (patient preferences, language barrier, patient condition, acknowledgment of cultural differences as sub-themes), and (d) AIDET in nursing education strengthening application through practice, optimizing frequency and timing, promoting deeper understanding, enhancing feedback mechanism) as student nurses’ recommendations. Conclusion: Early integration of AIDET in nursing education is essential for student nurses to enhance communication, improve patient satisfaction, and deliver patient-centered care, equipping them with valuable communication skills.